Interdiffusion coefficient and atomic mobility for fcc Ag-Cu-Mg phase at 1073 K - Du C.-B.; Huang S.-P.; Min Q.-H.; Liu Y.-L.; Wen S.-Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this work, the interdiffusion coefficient and atomic mobility for the fcc Ag-Cu-Mg phase at 1073 K were investigated by combining diffusion couple experiments and calculations. Based on the experimental composition profiles, the diffusion coefficients at the intersections of the diffusion paths were calculated using the Matano-Kirkaldy method. Using the thermodynamic descriptions available in the literature, the atomic mobilities for the fcc Ag-Cu-Mg phase were automatically optimized by numerical inverse method integrated with the CALTPP (CALculation of ThermoPhysical Properties) program. Moreover, the obtained atomic mobilities were confirmed to be reliable by good agreements between the model-simulated and the measured composition profiles. In addition, three-dimensional surfaces were presented for the interdiffusion coefficient, activation energy, and frequency factor. The presently obtained atomic mobilities can be incorporated into the diffusion database for Ag-based alloys, which can contribute to microstructure simulation and materials design.